BENTUK PERTUNJUKAN KETOPRAK SARI BUDOYO DALAM LAKON KI AGENG MANGIR - DELASARI, ANDRIS; ABDILLAH, AUTAR (APRON Jurnal Pemikiran Seni Pertunjukan, 2020)
THE FORM OF KETOPRAK SARI BUDOYO PLAY IN LAKON KI AGENG MANGIRByAndris DelasariE-mail : andrisdelasari16020134009@mhs.unesa.ac.id Dr. Autar Abdillah, S.Sn., M.Si.autarabdillah@unesa.ac.idEducational Sendratasik Department, Language and Art FacultyState University of Surabaya ABSTRACTTulungagung is one of East Java district which has traditional theater called Ketoprak. Ketoprak traditional theater is familiar to East Java society. One of the most famous ketoprak from Tulungagung is Ketoprak Siswo Budoyo who succeed in creating a breakthrough in the Ketoprak Play. However, as time passed by Ketoprak Siswo Budoyo existence began to fade until a new group of Ketoprak came up which still has relation with Ketoprak Siswo Budoyo owner and founder. The ketoprak is called Ketoprak Sari Budoyo.The Growth of Ketoprak Sari Budoyo is not as great as Ketoprak Siswo Budoyo. Nowadays, Ketoprak is rarely to be invited in certain events. In order to stage the play, the ketoprak group members should raise funds by themselves to make the play runs. That is in purpose since the young generation have to know the ancestor heritage and also to keep this traditional art. The Ketoprak Sari Budoyo play schedule is not routine but within a year it certainly has the show once.The research problems that studied are as follows: 1) How is the form of the Ketoprak Sari Budoyo play in the Lakon Ki Ageng Mangir ?. The researcher used qualitative method as the research design to describe the information by using data collection method: observation, interview and documentation. The researcher also used triangulation technique to examine the validity and reliability of the study. The result of the study showed that the form of Ketoprak Sari Budoyo play has its speciality which took the audiences interest to watch all over the play. Ketoprak Sari Budoyo uses Mataraman Style in the whole all its play, which in its performances the actor looks natural or not based on stage blocking, there is also keprak or kentongan that is used as a sign for the players entering and exiting the stage, as a sign for accompaniment starting and ending, and also some jokes during the play. Ketoprak Sari Budoyo is included breakthrough Ketoprak which did not have all night long play. This has been done to avoid the young generation boredom thus they could enjoy until the end of the play. Keywords : The Play Form, Ketoprak, Sari Budoyo, Lakon